The competences of the International Criminal Court and the conflict in Ukraine (Ius Novum, 2023)
The article is an essay to answer the question whether, in the light of the current Internalional Criminal Court’s in Hague rights, it is possible to hold Russian Federation accountable for international crimes. The answer to this question depends on the type of crimes committed, as some of them (such as the crime of aggression) should be considered as excluded from the jurisdiction of the ICC. The article also points to other possible ways of holding Russia accountable, such as the establishment of a special ad hoc tribunal, which is widely discussed, among others, in the European Parliament. The outcome of these discussions is a resolution of January 19, 2023.
Keywords: International Criminal Court; conflict in Ukraine; competences of ICC; the possibility of prosecuting Russian Federation